Relationship between Body Mass Index and Central Fat Accumulation in Adolescents in Surakarta - Wijaya, Angellica Eliora; Ayusari, Amelya Augusthina; Wiboworini, Budiyanti; Damayanti, Kusmadewi Eka (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Obesity diagnosis can be determined through the calculation of body mass index (BMI). However, BMI can only serve as a screening tool for obesity and can not measure fat distribution while waist-to-height ratio (WHtR) is considered better for determining central fat distribution in adolescents. The aim of this study is to examine the relationship between body mass index and central fat accumulation in adolescents in Surakarta.Methods: The method used was cross-sectional, involving measurements of weight, height, and waist circumference. The subjects of this study are tenth-grade adolescents from three high schools in Surakarta, with a total of 83 subjects. The variables in this study are the z-score of BMI-for-age (ratio) with waist circumference (ratio) and waist-to-height ratio (WHtR). Statistical analysis used the Spearman test.Results: The Spearman correlation analysis demonstrated a significant association between body mass index (BMI) and waist circumference (p < 0,001; r = 0,777), as well as BMI and WHtR (p < 0,001; r = 0,785).Conclusion: There is a strong positive relationship between body mass index and central fat accumulation among high school students in Surakarta.Keywords: adolescents; BMI; central fat; waist circumference; WHtR